LAND REGISTRATION AND SPORADIC COOPERATION POLICY - Sulistyowati Sulistyowati (Jurnal Pembaharuan Hukum, 2020)
This research aims tounderstand the complete systematic land registration policy and to understand the complete systematic land registration model at the Jepara Regency Land Office. The approach method used is sociological juridical and data collection is done using the interview method. The results of this study indicate that the complete systematic land registration policy has been implemented in a collaborative manner with sporadic registration, which is ultimately divided into 4 (four) clusters. This is because not all people agree with the Complete Systematic Land Registration program. Collaboration of the registration system is carried out in order to achievetarget group .